Bibliometric Analysis of Social Norms in Tax Compliance - Nur Cahyonowati (Jurnal Proaksi, 2024)
Apart from deterrence factors, social norms are crucial as non-formal institutions that provide guidelines for taxpayer behavior. Social interactions among taxpayers influence tax compliance decision making. This study aims to provide a bibliometric analysis of the term “social norms” in the tax compliance literature. This study analyzed articles published in the Scopus database using Publish or Perish (PoP), VOSviewer, MS Excel and Mendeley to organize and analyze the publications. This study analyzes the publications addressing the theme from 1987 until March 3, 2023. The 120 articles were screened from a more extensive original set of 136. This study found that since 2000, the number of publications has been on the rise and reached its peak in 2020. Using VOSviewer, research in this field is classified into nine clusters or research streams. This study has identified James Alm as the most productive and influential author in this field, and the article by Kirchler et al. (2008) as the most influential publication in this field.